Atorvastatin Treatment of Rats with Ischemia-Reperfusion Injury Improves Adipose-Derived Mesenchymal Stem Cell Migration and Survival via the SDF-1α/CXCR-4 Axis - Cai, Anping (Public Library of Science, 2013)
BACKGROUND: Adipose-derived mesenchymal stem cells (ASCs) transplantation is a promising approach for myocardium repair. Promotion of ASCs migration and survival is the key for improving ASCs efficiency. SDF-1α is a critical factor responsible for ASCs migration and survival. Atorvastatin (Ator) is capable of up-regulating SDF-1α. Therefore, we're going to investigate whether ASCs migration and survival could be improved with atorvastatin. METHODS: In vitro study, cardiomyocytes were subjected to anoxia-reoxygenation injury and subsequently divided into different groups: group blank control, Ator, Ator plus L-NAME (A+L-NAME) and Ator plus AMD3100 (A+AMD3100).When migration analysis completed, cardiomyocytes were used for subsequent analyses. In vivo study, rats underwent ischemia-reperfusion injury were assigned into different groups corresponding to in vitro protocols. ASCs were transplanted on the seventh day of atorvastatin therapy. Seven days later, the rates of migration, differentiation and apoptosis were evaluated. RESULTS: Compared with other groups, ASCs migration in vitro was significantly improved in group Ator, which was dependent on SDF-1α/CXCR-4 coupling. Results of in vivo study were consistent with that of in vitro study, further supporting the notion that the efficacy of atorvastatin on ASCs migration improvement was related to SDF-1α/CXCR-4 axis. Higher vessel density in group Ator might be another mechanism responsible for migration improvement. Concomitantly, apoptosis was significantly reduced in group Ator, whereas no significant difference of differentiation was found. CONCLUSION: Migration and survival of ASCs could be improved by atorvastatin under ischemia-reperfusion injury, which were ascribed to SDF-1α/CXCR-4 axis.